Evaluation of prognostic significance of lymphovascular space invasion in early stage endometrial cancer: a systematic review and meta-analysis - Qin, Zhao-juan; Wang, Yi-si; Chen, Ya-li; Zheng, Ai; Han, Ling (Frontiers in Oncology, 2024)
Background: Studies evaluating the prognostic significance of lymphovascular space invasion (LVSI) in early stage endometrial cancer (EC) are conflicting. Objectives: To evaluate whether LVSI identified in stage I EC is associated with worse survival. Search strategy: A comprehensive literature search of three databases (Embase, PubMed, and Cochrane) was performed up to April 30 th 2023. Selection criteria: Cohort studies that have evaluated the relationship between LVSI and prognosis in patients with stage I EC were included.Data collection and analysis: Two authors independently assessed the studies for inclusion, extracted the data of recurrence and survival, and conducted meta-analysis using random effects model. Heterogeneity was evaluated by I 2 test.Main results: A total of 15 studies involving 6,705 patients were included in the meta-analysis. The overall pooled rate of LVSI was 14% [95% confidence interval (CI) CI 0.09-0.18] in stage I EC. LVSI was significantly associated with a higher risk of recurrence [odds ratio (OR) = 2.79, 95%CI 2.07-3.77], reduced overall survival (OS)[hazard ratio (HR)=5.19, 95%CI 3.33-8.07] and recurrence free survival (RFS) [HR = 5.26,] in stage I EC patients. Similarly, LVSI was associated with an increased risk of recurrence [OR= 3.10, decreased OS [HR=5.52,] and RFS [HR = 4.81,] in stage IA grade 1 or 2 endometrioid carcinoma patients.The presence of LVSI in stage I EC and in stage IA, grade 1 or 2 endometrioid carcinoma is associated with an increased risk of recurrence, lower OS and RFS.